Carburos precipitados en una aleación Zr-2,5 Nb fundida - Piotrkowski, Rosa; Vigna, Gustavo; Bermúdez, S. E.; García, Enrique A. (Comisión Nacional de Energía Atómica; Argentina, 1993)
Fil: Piotrkowski, Rosa Comisión Nacional de Energía Atómica; Argentina